Integrasi Sistem Pengelolaan Sampah Berkelanjutan Berbasis WhatsApp chatbot di Desa Karangsono - Khoirin Maghfiroh; Mukhammad Ilham Mufid; Luluk Badriyah; Mas Muhammad Iwan Falik; Luluk Anisa; Hesty Nurlita Fauzia (Universitas Muhammadiyah Malang, 2026)
Purpose –The aim of activity to increase understanding of Karangsono Village community in managing waste independently at home and optimizing the role of waste banks and WDS as places for sustainable final waste management through digital technology. Design/methodology/approach – The program implementation stages include socialization, training, mentoring, and evaluation. The waste management system is centralized within the Village-Owned Enterprise (BUMDES) in Karangsono. Findings – According to the activity's results, 95%, 86%, 73%, and 93% respondents respectively, have increased their knowledge of how to distinguish, sort, and properly manage waste. Additionally, 69%, 82%, 78%, 89%, 78%, and 76% respondents have increased their awareness of how to manage household waste, use plastic bags, recycle plastic waste, and avoid piling up waste at home. Finally, 89%, 95%, 84%, 93%, 86%, 84%, and 86% respondents have an impact on aspects of village environment. The Owned Enterprise manages a Waste Bank and Waste Disposal Site (WDS) to facilitate direct waste management by collecting waste from the community. In addition to WDS, there are waste banks that manage dry waste through a savings system similar to that used in financial institutions. Originality/value – Digital technology in the form of WhatsApp Bots helps improve the efficiency of integrated waste management system at WDS and waste banks.